IMPLEMENTASI FATWA MAJELIS ULAMA INDONESIA TENTANG KEDUDUKAN WARIA DALAM KONTEKS OPERASI PERUBAHAN DAN PENYEMPURNAAN KELAMIN - oskar hutagaluh (Samawa (Sakinah, Mawaddah Warahmah), 2023)
The perfection of the human form still has various physical phenomena, some are physically perfect and genetically perfect. On the other hand, there are also humans who are born with imperfect physical and genetic forms. Reality shows that there are people who are born with intimate organs as perfect men, but look like women, usually called waria. Because there is a psychiatrist concerned who is not satisfied with his genitals. In this context, Islam allows and even encourages sex change for someone who has multiple genitals, penis and vagina, or has no genitals at all (khunsa), to clarify and function optimally and definitively one of the genitals because it will give the benefit is greater than the harm (mafsadat). This research is a field research (field research) which is qualitative in nature. Field research procedures that produce descriptive data, in the form of written or oral data from the people and research observed. Therefore in this study each symptom is associated withimplementation of the MUI fatwa regarding the position of waria in the context of sex change and perfecting operations.will be studied thoroughly and in depth and endeavored to provide a deep meaning of the phenomena found.